Study of Stability of Non-linear Model with Hyperbolic Secant Function - Anas Salim Youns Youns (مجلة التربية والعلم, 2019)
We study a new definition of a non-linear model of time series with hyperbolic secant function in a discrete time. The suggested model consist of two parts the first part is (linear) and the second part is (non-linear) which contains the hyperbolic secant function. We approximate this model to be linear by using the local linearization technique. We find the non-zero unique singular point that satisfies the non-linear variation equation, also stability of the non-zero unique singular point and the limit cycle if it exists of the suggested model.